Antioxidant and antidiabetic properties of Chinese and Indian bitter melons (Momordica charantia L.). (June 2019) - Wang, Li; Clardy, Arvazena; Hui, Dafeng; Gao, Aiwu; Wu, Ying
Abstract: Bitter melon ( Momordica charantia L.) has been used for anti-diabetes treatment for decades. Indian and Chinese bitter melons (BM) are two commonly produced cultivars in the US market. This study has comparatively evaluated the effects of two processing methods (fresh and freeze-drying) on Chinese and Indian BM by measuring their bioactivity in terms of total phenolic content (TPC), total triterpene content (TTC), antioxidant activity, and antidiabetic properties using the DPPH free radical scavenging and reducing power assays, and the α-amylase and α-glucosidase inhibition assays. The TPC (GAE mg/g dw) in freeze-dried BM were 6.03 and 6.09, and in fresh BM were 4.81 and 4.83 for Indian and Chinese BM, respectively. The TTC (OAE mg/g dw) in Indian BM were 7.25 and 5.63, and in Chinese BM were 5.88 and 3.87 for fresh and freeze-dried samples, respectively. TPC and TTC in the freeze-dried BM samples were significantly higher than that in the fresh ones ( p < 0.05). The DPPH IC50 of India BM was significantly lower than that of Chinese BM ( p < 0.05). All BM samples ranged from 9.18 to 18.6 mg/ml. The reducing power was significantly different between Indian and Chinese BM ( p < 0.01) for fresh samples, but after freeze-drying, there was no detectable difference in reducing power ( p ≥ 0.05). The Indian BM showed a significantly stronger α-glucosidase inhibition effect as compared to the Chinese BM. TTC was positively correlated with reducing power ( p < 0.05). TPC was negatively correlated with α-amylase inhibition efficiency ( p < 0.05).